2019
DOI: 10.1585/pfr.14.4406115
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gas Pressure on the Size Distribution and Structure of Carbon Nanoparticles Using Ar + CH<sub>4 </sub>Multi-Hollow Discharged Plasma Chemical Vapor Deposition<sup> </sup>

Abstract: Using an Ar + CH 4 multi-hollow discharge plasma chemical vapor deposition (MHDPCVD) method, carbon nanoparticles (CNPs) are synthesized in a size range between 10 nm and 100 nm at gas pressures from 2 Torr to 5 Torr. The size of the nanoparticles increases from 45.42 nm 3 at 2 Torr to 67.85 nm 3 at 5 Torr. The size dispersion also increases. Conversely, the optical emission intensities and generation of carbon related radicals decrease with increasing pressure. The Raman measurements indicate that these CNPs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 36 publications
(37 reference statements)
1
7
0
Order By: Relevance
“…Thus, d p was assumed to be equal to zero at t = 0, and the growth of CNPs stops at t = τ res . Figure 8 shows the dependence of d p on τ res , based on FR dependence, together with the results reported earlier [23]. Considering the larger size of CNPs for FR = 10 sccm, the size of CNPs linearly increases with increasing the τ res .…”
Section: Resultssupporting
confidence: 63%
See 4 more Smart Citations
“…Thus, d p was assumed to be equal to zero at t = 0, and the growth of CNPs stops at t = τ res . Figure 8 shows the dependence of d p on τ res , based on FR dependence, together with the results reported earlier [23]. Considering the larger size of CNPs for FR = 10 sccm, the size of CNPs linearly increases with increasing the τ res .…”
Section: Resultssupporting
confidence: 63%
“…The surface-modified nanoparticles showed multi-exciton generation, which is necessary to increase solar cells' efficiency [18]. We recently used MHDPCVD to produce carbon nanoparticles [23][24][25] and confirmed that pressure played an important role in size control [23]. These studies revealed the essential parameters for the size control, while the growth mechanism was unclear.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations